2021
DOI: 10.3389/fphar.2021.733420
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Promotes Functional Recovery After Spinal Cord Injury in Rats

Abstract: Spinal cord injury (SCI) is a devastating condition that results in severe motor, sensory, and autonomic dysfunction. The L-/T-type calcium channel blocker nimodipine (NMD) exerts a protective effect on neuronal injury; however, the protective effects of long-term administration of NMD in subjects with SCI remain unknown. Thus, the aim of this study was to evaluate the role of long-term treatment with NMD on a clinically relevant SCI model. Female rats with SCI induced by 25 mm contusion were subcutaneously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Few studies analysed the mechanisms of nimodipine actions in the CNS. After spinal cord injury, nimodipine-treated rats showed improvements in gliosis, CGRP+ fibre sprouting, and an increased KCC2 expression in lumbar motor neurons [ 67 ]. Furthermore, nimodipine downregulated lncRNA nuclear paraspeckle assembly transcript 1, upregulated miR-27a, downregulated microtubule associated protein tau, inhibited brain tissue cell apoptosis and enhanced brain cell activity, resulting in improved outcomes and cognitive performance [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies analysed the mechanisms of nimodipine actions in the CNS. After spinal cord injury, nimodipine-treated rats showed improvements in gliosis, CGRP+ fibre sprouting, and an increased KCC2 expression in lumbar motor neurons [ 67 ]. Furthermore, nimodipine downregulated lncRNA nuclear paraspeckle assembly transcript 1, upregulated miR-27a, downregulated microtubule associated protein tau, inhibited brain tissue cell apoptosis and enhanced brain cell activity, resulting in improved outcomes and cognitive performance [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies in the future with nimodipine might provide further evidence for its use in SCI (Table 3). 125 Likewise, case reports suggest that ziconotide, by blocking N-type calcium channels, could also relieve spasticity-mediated pain post-SCI. (Table 4).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…A recent study in SCI rats demonstrated that long-term administration of nimodipine reduced pain and spasticity, raised KCC2 expression, spared neurons with the overall promotion of functional recovery. Additional studies in the future with nimodipine might provide further evidence for its use in SCI ( Table 3 ) [ 125 ]. Likewise, case reports suggest that ziconotide, by blocking N-type calcium channels, could also relieve spasticity-mediated pain post-SCI.…”
Section: Restoring the Inhibitory Tone Relieves Sci-spasticitymentioning
confidence: 99%
“… 6 , 8 , 9 Nimodipine, an L−/T‐type VGCC blocker, can prevent spasticity in SCI rodents when administered beforehand 10 and can promote the functional recovery in SCI rats. 11 Also, the T‐type VGCC, which is thought to be mainly implicated in pain transmission and sensitization, involves the remodeling of neuronal and reflex excitability after SCI. 12 Previous studies have reported that the expression of T and L VGCCs was changed after SCI, which might be associated with the functional alterations of neurons.…”
Section: Introductionmentioning
confidence: 99%